THE SOCIAL ASPECT OF THE USAGE OF PUPILS' SELF-EXPRESSION SKILLS ACQUIRED WITHIN MUSIC EDUCATION - Kepule, Iveta; STRODE, AINA (Journal of Education Culture and Society, 2020)
Aim. The aim of the research is to study the usage of primary school pupils’ self-expression skills acquired within music education in various social contexts.Methods. Theoretical research method – the analysis of literature, empirical data acquisition method – questionnaire. Statistical data processing has been carried out in IBM SPSS 23 programme, using the following data processing methods: frequency analysis; Mann-Whitney U test for the comparison of two independent groups; Kruskal-Wallis test for the comparison of three or more independent groups; Kendall rank correlation coefficient for the assessment of associations between two variables.Results. In the development of self-expression skills, an important aspect is the social performance criterion that is based on pupils’ need for self-expression in a social environment of practising music. Age and gender-based correlations in the assessment of a self-expression skill criterion "Social performance" indicate that with age pupils become more independent and engaged in music-related social activities. Girls are socially more active and emotional and engage in artistic activities more often. The research confirms the role of teachers in the development of pupils’ self-expression skills, promoting integration of formal and informal learning process and transformation in formal and informal learning environment.Conclusions. The dynamics and interactions of self-expression skills’ development factors (social, emotional and intellectual) defines pupils’ individual self-expression skills and development tendencies. Self-expression is important for pupils in social aspect, as it is related to socialisation in microenvironment (family) and macroenvironment (friends) and affects cooperation and communication.